A composite phase-change thermal storage material and a preparation method thereof

By eutecticizing dimethyl fumarate and carboyldiamine, adding thermal conductivity and nucleating agents, composite phase change heat storage materials are prepared, which solves the problems of reducing heat storage capacity and safety risks of existing phase change energy storage materials under high temperature conditions, and achieves efficient and stable thermal energy storage and release.

CN115895603BActive Publication Date: 2025-04-11PREGIS NEW MATERIALS (SHENZHEN) PTE LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211633494.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-04-11
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

Existing phase change energy storage materials can easily lead to reduced heat storage capacity, shortened service life, and there are problems of corrosion and safety risks under high temperature conditions.

Method used

Dimethyl fumarate and carboamyldiamine were used as main raw materials for eutectics, combined with thermal conductivity and nucleating agents, and a composite phase change heat storage material was prepared. The phase change temperature was between 69 and 91°C, with high safety, high thermal enthalpy and good thermal stability.

Benefits of technology

The phase transition temperature is optimized, the thermal conductivity and thermal stability of the material are improved, the service life of the material is extended, and the floor area of ​​the heat storage equipment is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115895603B_ABST
    Figure CN115895603B_ABST
Patent Text Reader

Abstract

The invention discloses a composite phase-change heat storage material and a preparation method thereof. The composite phase-change heat storage material comprises the following raw materials in parts by mass: 50-70 parts of dimethyl fumarate, 25-40 parts of carbamide, 0.1-15 parts of heat-conducting material and 0.1-4 parts of nucleating agent; the preparation method comprises mixing dimethyl fumarate, carbamide, heat-conducting material and nucleating agent; the composite phase-change heat storage material has a phase change temperature of 69-91°C and a thermal enthalpy of 160-230 J / g; after 1000 cycles, the thermal performance attenuation of the phase-change heat storage material is less than 20%, the thermal stability is good, and the supercooling degree is less than 2°C; after adding the heat-conducting material, the thermal conductivity of the composite phase-change heat storage material is increased by 1.9-16 times compared with that when no heat-conducting material is added; the preparation process is simple, the raw materials are easy to obtain, and the composite phase-change heat storage material is suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phase change materials, and in particular to a composite phase change heat storage material and a preparation method thereof. Background Art

[0002] Phase change energy storage is considered to be a very promising energy storage method because of its high energy storage density, constant phase change temperature and wide availability of phase change materials. In the field of medium and low temperature heat storage, hydrated salt phase change energy storage materials are a type of material with excellent performance. Among them, barium hydroxide octahydrate has the highest latent heat, stable performance, and the phase change temperature is most suitable for medium and low temperature. However, this material is strongly alkaline in the molten state, and it is easy to cause greater corrosion to general metal containers in the high-temperature molten state, resulting in leakage; there are also magnesium nitrate hexahydrate and lithium nitrate as the main latent heat materials, but their phase change enthalpy values ​​are low and the cost of lithium nitrate is high; there are also composites of ammonium aluminum sulfate dodecahydrate and stearic acid as the main phase change latent heat materials, but ammonium aluminum sulfate dodecahydrate has strong acidity and there is a risk of safety in use. Moreover, all of the above are inorganic hydrated salts. Under high temperature conditions, the volatilization and phase separation of crystalline water of inorganic hydrated salts will lead to a decrease in the heat storage capacity of the heat storage material and a shortened lifespan, which will further affect the application research and promotion of the material. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a composite phase change thermal storage material and a preparation method thereof in view of the defects of the prior art.

[0004] The technical solution adopted by the present invention to solve its technical problem is: a composite phase change heat storage material, comprising the following raw materials in parts by weight: 50-70 parts of dimethyl fumarate, 25-40 parts of carbamide, 0.1-15 parts of thermal conductive material and 0.1-4 parts of nucleating agent.

[0005] Furthermore, the raw materials preferably include the following parts by mass: 55-65 parts of dimethyl fumarate, 30-35 parts of carbamide, 6-10 parts of thermal conductive material and 2-3 parts of nucleating agent.

[0006] Furthermore, it is preferred that the thermally conductive material is a powdery or granular thermally conductive material; and / or the thermally conductive material is a foamed thermally conductive material.

[0007] Furthermore, it is preferred that the powdered or granular thermally conductive material is one or more of graphite, expanded graphite, graphene, graphene oxide, carbon nanotubes, silicon carbide, nanosilver and nanocopper.

[0008] Furthermore, it is preferred that the foam-like thermally conductive material is one or more of foam copper and foam aluminum.

[0009] Furthermore, preferably, the particle sizes of the carbon nanotubes, nanosilver and nanocopper are all 10 to 500 nm; the particle sizes of the graphite, the expanded graphite, the graphene and the graphene oxide are all 20 to 200 meshes, and the expansion multiple of the expanded graphite is 50 to 200 times.

[0010] Furthermore, preferably, the pore diameters of the foam copper and the foam aluminum are both 0.1-10 mm, and the porosity is 50-98%.

[0011] Furthermore, it is preferred that the nucleating agent is one or more of silicon dioxide, aluminum oxide, diatomaceous earth, activated carbon and foamed carbon.

[0012] Furthermore, it is preferred that the silicon dioxide is one or more of fumed silicon dioxide, nano silicon dioxide, and ordinary silicon dioxide.

[0013] Furthermore, it is preferred that the phase change temperature of the composite phase change thermal storage material is 69-91°C.

[0014] The present invention also provides a method for preparing a composite phase-change thermal storage material, comprising the following steps:

[0015] S1, take a foamed heat-conductive material and process it until it matches the storage space of the target heat storage container, fill the foamed heat-conductive material into the target heat storage container for standby use; take 50-70 parts of dimethyl fumarate, 25-40 parts of carbonyl diamide and powdered or granular heat-conductive material by mass, wherein the total mass of the foamed heat-conductive material and the powdered or granular heat-conductive material is 0.1-15 parts, stir and mix evenly to obtain a first mixed dry material;

[0016] Alternatively, 0.1 to 15 parts of foamed heat-conducting material are processed by weight until the foamed heat-conducting material matches the storage space of the target heat storage container, and the foamed heat-conducting material is filled into the target heat storage container for standby use; 50 to 70 parts of dimethyl fumarate and 25 to 40 parts of carbamide are taken by weight, and the mixture is stirred and mixed to obtain a first mixed dry material;

[0017] Alternatively, 50 to 70 parts by mass of dimethyl fumarate, 25 to 40 parts by mass of carbamide and 0.1 to 15 parts by mass of powdered or granular thermal conductive material are mixed and stirred to obtain a first mixed dry material;

[0018] S2, heating the first mixed dry material to 140-175° C. to melt and form a liquid homogeneous phase;

[0019] S3. Adjust the temperature of the liquid homogeneous phase to 90-120° C., add 0.1-4 parts of a nucleating agent, and stir evenly; then pour into a target heat storage container to obtain a composite phase change heat storage material.

[0020] Beneficial effects of the present invention: The present invention provides a composite phase-change heat storage material, which is obtained by eutectic with dimethyl fumarate and carbodiamide as main raw materials, which makes up for the problems of too small or too large phase change temperature, reduced phase change latent heat, and poor cycle stability when using a single phase change material, which leads to the inability to match the corresponding application field; the synthesized phase change temperature point is 69-91°C, which is lower than the phase change point of the two pure materials (dimethyl fumarate is 102°C, and the phase change temperature of carbodiamide is 130°C), the synthesized phase change material temperature range is lower than 100°C, the safety factor is high, and it can be applied to systems with water as a heat exchange medium. At the same time, the higher heat storage temperature also means that the use temperature transmitted to the energy-consuming terminal is high, which broadens the application field. The thermal enthalpy value of the phase change heat storage material is 160-230 J / g, and the higher unit energy density will reduce the footprint of the heat storage equipment. After 1000 cycles, the thermal performance decay of the phase change heat storage material is less than 20%, and its thermal stability is good. After adding thermal conductive materials to the system, the thermal conductivity coefficient is increased by 1.9 to 16 times compared with the composite material without adding thermal conductive materials. The addition of nucleating agents reduces the supercooling to less than 2°C. The addition of thermal conductive enhancing materials and nucleating agents not only significantly improves the thermal conductivity of the material system, but also increases the heat release temperature and heat release efficiency.

[0021] The raw materials of the composite phase-change heat storage material of the present invention are easy to obtain, the process is simple, and it is suitable for batch production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a curve chart of differential scanning calorimeter test results of the composite phase change thermal storage material of Example 1 of the present invention;

[0023] Figure 2 is a step cooling curve diagram of the composite phase change thermal storage material of Example 1 of the present invention;

[0024] Figure 3 is a curve chart of differential scanning calorimeter test results of the composite phase change thermal storage material of Example 2 of the present invention;

[0025] Figure 4 is a step cooling curve diagram of the composite phase change thermal storage material of Example 2 of the present invention;

[0026] Figure 5 is a curve chart of differential scanning calorimeter test results of the composite phase change thermal storage material of Example 3 of the present invention;

[0027] Figure 6 is a step cooling curve diagram of the composite phase change thermal storage material of Example 3 of the present invention;

[0028] Figure 7 is a curve chart of differential scanning calorimeter test results of the composite phase change thermal storage material of Example 4 of the present invention;

[0029] Figure 8 is a step cooling curve diagram of the composite phase change thermal storage material of Example 4 of the present invention;

[0030] Fig. 9 is a curve chart of differential scanning calorimeter test results of the composite phase change thermal storage material of Example 5 of the present invention;

[0031] Fig.10 It is a step cooling curve diagram of the composite phase change thermal storage material of Example 5 of the present invention. DETAILED DESCRIPTION

[0032] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific embodiments of the present invention are now described in detail.

[0033] The composite phase-change heat storage material of the present invention comprises the following raw materials in parts by mass: 50 to 70 parts of dimethyl fumarate, 25 to 40 parts of carbamide, 0.1 to 15 parts of heat-conducting material and 0.1 to 4 parts of nucleating agent.

[0034] The present invention provides a composite phase-change heat storage material. The phase-change material of the present invention is obtained by eutectic with dimethyl fumarate and carbodiamide as main raw materials, which makes up for the problems of too small or too large phase change temperature, reduced phase change latent heat, and poor cycle stability when using a single phase-change material, which leads to the inability to match the corresponding application field; the synthesized phase change temperature point is 69-91°C, which is lower than the phase change point of the two pure materials (dimethyl fumarate is 102°C, and the phase change temperature of carbodiamide is 130°C). The synthesized phase change material has a temperature range of less than 100°C, a high safety factor, and can be applied to systems with water as a heat exchange medium. At the same time, a higher heat storage temperature also means that the use temperature transmitted to the energy-consuming terminal is high, which broadens the application field. The thermal enthalpy value of the phase-change heat storage material is 160-230 J / g, and a higher unit energy density will reduce the footprint of the heat storage equipment. After 1000 cycles, the thermal performance decay of the phase-change heat storage material is less than 20%, and its thermal stability is good. The addition of thermal conductive materials into the system increases the thermal conductivity by 1.9 to 16 times compared with the composite material without thermal conductive materials. The addition of nucleating agents reduces the supercooling to less than 2°C. The addition of thermal conductive materials and nucleating agents not only significantly improves the thermal conductivity of the material system, but also increases the heat release temperature and heat release efficiency.

[0035] In some specific embodiments, the composite phase-change thermal storage material includes the following raw materials in parts by weight: 55-65 parts of dimethyl fumarate, 30-35 parts of carbamide, 6-10 parts of thermal conductive material and 2-3 parts of nucleating agent.

[0036] Furthermore, the heat-conducting material is preferably a powder or granular heat-conducting material; or, the heat-conducting material is a foam heat-conducting material; or, the heat-conducting material includes a foam heat-conducting material and a powder or granular heat-conducting material. Adding a heat-conducting material is beneficial to improving the thermal conductivity of the phase-change thermal storage material, so that the thermal conductivity is increased by 1.9 to 16 times compared with the pure material (pure dimethyl fumarate and pure carbon diamide), shortening the heat storage time and improving the heat release efficiency.

[0037] Furthermore, the powdered or granular thermally conductive material is preferably one or more of graphite, expanded graphite, graphene, graphene oxide, carbon nanotubes, silicon carbide, nanosilver and nanocopper.

[0038] Furthermore, it is preferred that the foamed thermally conductive material is one or more of foamed copper and foamed aluminum.

[0039] Furthermore, it is preferred that the particle sizes of carbon nanotubes, nanosilver and nanocopper are all 10 to 500 nm; the particle sizes of graphite, expanded graphite, graphene and graphene oxide are all 50 to 200 meshes, and the expansion coefficient of expanded graphite is 50 to 200 times; the pore sizes of foamed copper and foamed aluminum are all 0.1 to 10 mm, and the porosity is 50 to 98%. Controlling the particle size of powdered or granular thermal conductive materials and the pore size of foamed thermal conductive materials is conducive to uniformly dispersing the thermal conductive materials in the system, which is conducive to improving the thermal conductivity of phase change thermal storage materials, shortening the thermal storage time, and improving the heat release efficiency.

[0040] Further, the preferred nucleating agent is one or more of silica, alumina, diatomaceous earth, activated carbon and foamed carbon. Further, the preferred silica is one or more of fumed silica, nano silica and ordinary silica. By the non-uniform nucleation mechanism, adding a nucleating agent to the phase change system of the present invention can effectively reduce the supercooling of the phase change material, and this requires that the nucleating agent matches the crystal structure characteristics, lattice parameter size, physical properties and other aspects between dimethyl fumarate and carboxamide, and is combined with the addition of a thermal conductive material; the nucleating agent is used to play a role as a crystal nucleus in the phase change process of the phase change material, promote crystal growth, and reduce the barrier of nucleation growth; at the same time, the nucleating agent used above can also be used as a high thermal conductivity material, and is used together with a thermal conductive material to improve the thermal conductivity of the phase change material system, thereby increasing the heat exchange rate and controlling the temperature more quickly.

[0041] Furthermore, the phase change temperature of the composite phase change thermal storage material is 69-91°C.

[0042] The present invention also provides a method for preparing a composite phase-change heat storage material. When the heat-conducting material includes a powdery or granular heat-conducting material and a foamed heat-conducting material, the method specifically includes the following steps:

[0043] S1, take a foamed heat-conductive material and process it until it matches the storage space of the target heat storage container, that is, the shape and size of the foamed heat-conductive material are basically the same as the shape and size of the storage space, and fill the foamed heat-conductive material into the target heat storage container for standby use; take 50-70 parts of dimethyl fumarate, 25-40 parts of carbonyl diamide and powdered or granular heat-conductive material by mass, wherein the total mass of the foamed heat-conductive material and the powdered or granular heat-conductive material is 0.1-15 parts, stir and mix evenly to obtain a first mixed dry material;

[0044] S2, heating the first mixed dry material to 140-175° C. to melt and form a liquid homogeneous phase;

[0045] S3. Adjust the temperature of the liquid homogeneous phase to 90-120°C, add 0.1-4 parts of nucleating agent, stir evenly to obtain a mixed solution; and pour the mixed solution into a target heat storage container filled with foamed heat conductive material, and the mixed solution quickly and evenly diffuses in the pores of the foamed heat conductive material to obtain a composite phase change heat storage material.

[0046] The present invention also provides a method for preparing a composite phase-change heat storage material. When the heat-conducting material is a foam-like heat-conducting material, the method comprises the following steps:

[0047] S1, taking 0.1 to 15 parts by mass of foamed heat-conducting material for processing, processing to match the storage space of the target heat storage container, that is, the shape and size of the foamed heat-conducting material are basically the same as the shape and size of the storage space, filling the foamed heat-conducting material into the target heat storage container for standby use; taking 50 to 70 parts by mass of dimethyl fumarate and 25 to 40 parts of carbamide diamide, stirring and mixing them evenly to obtain a first mixed dry material;

[0048] S2, heating the first mixed dry material to 140-175° C. to melt and form a liquid homogeneous phase;

[0049] S3. Adjust the temperature of the liquid homogeneous phase to 90-120°C, add 0.1-4 parts of nucleating agent, stir evenly to obtain a mixed solution; and pour the mixed solution into a target heat storage container filled with foamed heat conductive material, and the mixed solution quickly and evenly diffuses in the pores of the foamed heat conductive material to obtain a composite phase change heat storage material.

[0050] The present invention also provides a method for preparing a composite phase-change heat storage material. When the heat-conducting material is a powdery or granular heat-conducting material, the method comprises the following steps:

[0051] S1, taking 50-70 parts by mass of dimethyl fumarate, 25-40 parts by mass of carbamide and 0.1-15 parts by mass of powdered or granular thermal conductive material, stirring and mixing them evenly to obtain a first mixed dry material;

[0052] S2, heating the first mixed dry material to 140-175° C. to melt and form a liquid homogeneous phase;

[0053] S3. Adjust the temperature of the liquid homogeneous phase to 90-120° C., add 0.1-4 parts of a nucleating agent, stir evenly, and obtain a mixed solution; and pour the mixed solution into a target heat storage container to obtain a composite phase change heat storage material.

[0054] The present invention is further explained below through specific examples.

[0055] Example 1

[0056] A composite phase-change heat storage material comprises the following raw materials in parts by mass: 50 parts of dimethyl fumarate, 40 parts of carbamide, 6 parts of expanded graphite (about 100 meshes), and 4 parts of fumed silicon dioxide.

[0057] Among them, expanded graphite can be replaced by at least one of graphite, graphene, graphene oxide, carbon nanotubes, silicon carbide, nanosilver and nanocopper, or a mixture thereof; silicon dioxide can be replaced by at least one of alumina, diatomaceous earth, activated carbon and foamed carbon, or a mixture thereof.

[0058] The preparation method of the composite phase change thermal storage material comprises the following steps:

[0059] S1, take 50 parts of dimethyl fumarate, 40 parts of carbamide and 6 parts of expanded graphite in proportion, add them into a dry material mixing equipment, and stir until they are uniformly mixed to obtain a first mixed dry material;

[0060] S2, adding the first mixed dry material into the reaction kettle, heating to 150° C., and melting to form a liquid homogeneous phase;

[0061] S3. Adjust the temperature of the liquid homogeneous phase to 100° C., add 4 parts of silicon dioxide, stir evenly, and pour into the target heat storage container to obtain a composite phase change heat storage material.

[0062] The composite phase change thermal storage material obtained above was tested by differential scanning calorimeter. The results are as follows: Figure 1 As shown, the phase transition temperature is 69.57℃, and the thermal enthalpy is 185J / g; the cooling curve (such as Figure 2 The thermal conductivity is 6.7W / (mK), which is 16 times higher than the thermal conductivity of pure material (0.42 / (mK). After the material is cycled 1000 times, the energy attenuation rate is 17%.

[0063] Example 2

[0064] A composite phase-change heat storage material comprises the following raw materials in parts by mass: 70 parts of dimethyl fumarate, 25 parts of carbamide, 2 parts of nano copper and 3 parts of fumed silicon dioxide.

[0065] The preparation method of the composite phase change thermal storage material comprises the following steps:

[0066] S1, taking 70 parts of dimethyl fumarate, 25 parts of carbamide and 2 parts of nano copper in proportion, adding them into a dry material stirring device, stirring until a uniform mixing state, to obtain a first mixed dry material;

[0067] S2, adding the first mixed dry material into the reaction kettle, heating to 175° C., and melting to form a liquid homogeneous phase;

[0068] S3. Adjust the temperature of the liquid homogeneous phase to 120° C., add 3 parts of silicon dioxide, stir evenly, and pour into the target heat storage container to obtain a composite phase change heat storage material.

[0069] The composite phase change thermal storage material obtained above was tested by differential scanning calorimeter. The results are as follows: Figure 3 As shown, the phase transition temperature is 90.8℃, the thermal enthalpy is 230J / g, and the cooling curve ( Figure 4 ) shows that the supercooling is 2.1℃ and the thermal conductivity is 1.2W / (mk), which is 2.85 times that of pure material. After the material is cycled 1000 times, the energy attenuation rate is 13%.

[0070] Example 3

[0071] A composite phase-change heat storage material comprises the following raw materials in parts by mass: 55 parts of dimethyl fumarate, 27 parts of carbamide, 2 parts of graphene oxide, 3 parts of aluminum oxide, and 13 parts of foam copper.

[0072] Among them, foam copper can be replaced by foam aluminum or a mixture thereof; graphene oxide can be replaced by at least one of graphite, expanded graphite, graphene, carbon nanotubes, silicon carbide, nanosilver and nanocopper or a mixture thereof; aluminum oxide can be replaced by at least one of silicon dioxide, diatomaceous earth, activated carbon and foam carbon or a mixture thereof.

[0073] The preparation method of the composite phase change thermal storage material comprises the following steps:

[0074] S1, processing 13 parts of copper foam until it matches the storage space of the target heat storage container, placing the copper foam in the target heat storage container for standby; taking 55 parts of dimethyl fumarate, 27 parts of carboxamide, and 2 parts of graphene oxide, stirring and mixing them evenly to obtain a first mixed dry material;

[0075] S2, heating the first mixed dry material to 140° C. to melt and form a liquid homogeneous phase;

[0076] S3. Adjust the temperature of the liquid homogeneous phase to 90°C, add 3 parts of aluminum oxide, stir evenly to obtain a mixed solution; pour the mixed solution into the target heat storage container with foam copper, and the mixed solution quickly and evenly diffuses in the pores of the foam-like thermal conductive material to obtain a composite phase change thermal storage material.

[0077] The composite phase change thermal storage material obtained above was tested by differential scanning calorimeter, and the results are as follows Figure 5 As shown, the phase transition temperature is 80.1℃, the thermal enthalpy is 205J / g, and the cooling curve ( Figure 6 ) shows that the supercooling is 0.2℃ and the thermal conductivity is 2.2W / (mk), which is 5.23 times that of pure material. After the material is cycled 1000 times, the energy attenuation rate is 12%.

[0078] Example 4

[0079] A composite phase-change heat storage material comprises the following raw materials in parts by mass: 65 parts of dimethyl fumarate, 34.8 parts of carbodiimide, 0.1 parts of nano silver, and 0.1 parts of fumed silicon dioxide.

[0080] The preparation method of the composite phase change thermal storage material comprises the following steps:

[0081] S1, taking 65 parts of dimethyl fumarate, 34.8 parts of carbamide and 0.1 parts of nano silver in proportion, adding them into a dry material stirring device, stirring until a uniform mixing state, to obtain a first mixed dry material;

[0082] S2, adding the first mixed dry material into the reaction kettle, heating to 145° C., and melting to form a liquid homogeneous phase;

[0083] S3. Adjust the temperature of the liquid homogeneous phase to 100° C., add 0.1 parts of silicon dioxide, stir evenly, and pour into the target heat storage container to obtain a composite phase change heat storage material.

[0084] The composite phase change thermal storage material obtained above was tested by differential scanning calorimeter, and the results are as follows Figure 7 As shown, the phase transition temperature is 74.9℃, the thermal enthalpy is 198J / g, and the cooling curve ( Figure 8 ) shows that the supercooling is 1.9℃ and the thermal conductivity is 0.8W / (mk), which is 1.9 times that of pure material. After the material is cycled 1000 times, the energy attenuation rate is 15%.

[0085] Example 5

[0086] A composite phase-change heat storage material comprises the following raw materials in parts by mass: 60 parts of dimethyl fumarate, 28 parts of carbodiimide, 10 parts of foamed aluminum and 2 parts of activated carbon.

[0087] The preparation method of the composite phase change thermal storage material comprises the following steps:

[0088] S1, take 0 parts of foam aluminum for processing, process it to match the storage space of the target heat storage container, fill the foamed heat conductive material into the target heat storage container for standby; take 60 parts of dimethyl fumarate and 28 parts of carbamide in proportion, add them to the dry material mixing equipment, stir until uniformly mixed, and obtain the first mixed dry material;

[0089] S2, adding the first mixed dry material into the reaction kettle, heating to 150° C., and melting to form a liquid homogeneous phase;

[0090] S3. Adjust the temperature of the liquid homogeneous phase to 100°C, add 2 parts of activated carbon, stir evenly, and pour into the target heat storage container to obtain the composite phase change heat storage material.

[0091] The composite phase change thermal storage material obtained above was tested by differential scanning calorimeter, and the results are as follows Fig. 9 As shown, the phase transition temperature is 73.5℃, the thermal enthalpy is 194J / g, and the cooling curve ( Fig.10 ) shows a supercooling degree of 1.6°C and a thermal conductivity of 3.1W / (mk), which is 7.3 times that of pure material. After the material is cycled 1000 times, the energy attenuation rate is 15%.

[0092] The present invention uses two organic phase change materials as the main substrate, and obtains a composite phase change thermal storage material by compounding, and matching with a heat conductive material and a nucleating agent. The phase change temperature point is 69-91°C, which is lower than the phase change point of the two pure materials (the phase change point of dimethyl fumarate is 102°C, and the phase change point of carbon diamide is 130°C). The synthesized composite phase change thermal storage material has a temperature range of less than 100°C, a high safety factor, and can be applied to systems where water is used as a heat exchange medium. At the same time, a higher heat storage temperature also means that the use temperature transmitted to the energy-consuming terminal is high, which broadens the application field. The thermal enthalpy value of the composite phase change thermal storage material is 160-230 J / g, and the higher unit energy density will reduce the footprint of the thermal storage equipment. After 1000 cycles, the thermal performance decay of the material is less than 20%, and its thermal stability is good. The addition of thermal conductive materials increases the thermal conductivity by 1.9 to 16 times compared to when no thermal conductive materials are added. The addition of nucleating agents reduces the supercooling to within 2°C, which increases the heat release above the effective temperature, thereby improving the heat storage and heat release efficiency accordingly.

[0093] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A composite phase change thermal storage material, characterized in that: The invention comprises the following raw materials in parts by weight: 50 to 70 parts of dimethyl fumarate, 25 to 40 parts of carbamide, 0.1 to 15 parts of thermal conductive material and 0.1 to 4 parts of nucleating agent.

2. The composite phase change thermal storage material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 55 to 65 parts of dimethyl fumarate, 30 to 35 parts of carbamide, 6 to 10 parts of thermal conductive materials and 2 to 3 parts of nucleating agents.

3. The composite phase change thermal storage material according to claim 1 or 2, characterized in that: The heat-conducting material is a powdery or granular heat-conducting material; and / or, the heat-conducting material is a foamed heat-conducting material.

4. The composite phase change thermal storage material according to claim 3, characterized in that: The powdered or granular thermal conductive material is one or more of graphite, expanded graphite, graphene, graphene oxide, carbon nanotubes, silicon carbide, nanosilver and nanocopper.

5. The composite phase change thermal storage material according to claim 4, characterized in that: The foamed heat-conducting material is one or more of foamed copper and foamed aluminum.

6. The composite phase change thermal storage material according to claim 4, characterized in that: The particle sizes of the carbon nanotubes, nanosilver and nanocopper are all 10-500 nm; the particle sizes of the graphite, expanded graphite, graphene and graphene oxide are all 50-200 meshes, and the expansion multiple of the expanded graphite is 50-200 times.

7. The composite phase change thermal storage material according to claim 5, characterized in that: The pore diameters of the foam copper and the foam aluminum are both 0.1-10 mm, and the porosity is 50-98%.

8. The composite phase change thermal storage material according to claim 1 or 2, characterized in that: The nucleating agent is one or more of silicon dioxide, aluminum oxide, diatomaceous earth, activated carbon and foamed carbon.

9. The composite phase change thermal storage material according to claim 8, characterized in that: The silicon dioxide is one or more of fumed silicon dioxide, nano silicon dioxide and common silicon dioxide.

10. The composite phase change thermal storage material according to any one of claims 1, 2, 4-7 or 9, characterized in that: The phase change temperature of the composite phase change thermal storage material is 69-91°C.

11. A method for preparing a composite phase-change thermal storage material, characterized in that: The following steps are involved: S1, take a foamed heat-conductive material and process it until it matches the storage space of the target heat storage container, fill the foamed heat-conductive material into the target heat storage container for standby use; take 50-70 parts of dimethyl fumarate, 25-40 parts of carbonyl diamide and powdered or granular heat-conductive material by mass, wherein the total mass of the foamed heat-conductive material and the powdered or granular heat-conductive material is 0.1-15 parts, stir and mix evenly to obtain a first mixed dry material; Alternatively, 0.1 to 15 parts by mass of foamed heat-conducting material are processed until the foamed heat-conducting material matches the storage space of the target heat storage container, and the foamed heat-conducting material is filled into the target heat storage container for standby use; 50 to 70 parts by mass of dimethyl fumarate and 25 to 40 parts by mass of carbodiamide are taken, stirred and mixed evenly to obtain a first mixed dry material; Alternatively, 50 to 70 parts by mass of dimethyl fumarate, 25 to 40 parts by mass of carbodiamide and 0.1 to 15 parts of powdered or granular heat-conducting material are taken, stirred and mixed evenly to obtain a first mixed dry material; S2. Heat the first mixed dry material to 140-175°C to melt and form a liquid homogeneous phase; S3. Adjust the temperature of the liquid homogeneous phase to 90-120°C, add 0.1-4 parts of a nucleating agent, and stir evenly; then pour into a target heat storage container to obtain a composite phase change heat storage material.

Citation Information

Patent Citations

  • Reinforced conductive composite phase-change heat storage material and preparation method thereof

    CN102286268A

  • Phase change energy storage material wall thermal insulation system

    CN106592791A